A Study of Awareness and Perception Regarding MOOC Courses with Special Reference to NPTEL - Arora, Amit Kumar; Kumar, Santosh; Bansal, Deepak; Bansal, Swati (Prabandhan: Indian Journal of Management, 2024)
Purpose : The study aimed to determine the level of awareness among students regarding NPTEL MOOCs and the reasons for registering or not registering for the courses. Further, this study explored the impact of gender and qualification on the category of aware respondents. Methodology : The study was a cross-sectional study for which data were collected from the Delhi-NCR region from January to March 2023. The study was based on primary data, considering 379 responses that were collected with the help of a structured questionnaire. The chi-square test and descriptive statistics were used to analyze the data. Findings : The study found that receiving the certificate, being more convenient regarding timing and location, and having command over the subject were the perceived benefits of doing NPTEL courses. The main reasons for not finishing the course were time constraints, students’ poor course selection, and loss of momentum as the course progressed. Gender was found to be independent of the category of aware respondents, while qualification was not found to be independent. Practical Implications : It was recommended that universities, colleges, and teachers adopt blended learning, which included e-learning as well as face-to-face learning, to help students score more. The NPTEL course providers and teachers should spread awareness regarding the courses, as 31% of the respondents were not aware of NPTEL. The study recommended that students be more careful while choosing the course and complete the course to earn the certificate, which can enhance their curriculum and, in turn, help them get a good job. Originality : Unlike prior research on the utility of MOOCs, the current work examined the learner’s perception toward the NPTEL courses conducted by the premium institutions in India.